Design, Analysis, Prototyping, and Experimental Evaluation of an Efficient Double Coil Magnetorheological Valve. (11th May 2014) - Hu, Guoliang; Long, Ming; Huang, Ming; Li, Weihua
Abstract : A double coil magnetorheological (MR) valve with an outer annular resistance gap was designed and prototyped. The finite element modeling and analysis of double coil MR valve were carried out using ANSYS/Emag software, and the optimal magnetic field distribution and magnetic flux density of the double coil MR valve were achieved. The mechanism of the pressure drop was studied by building a mathematical model of pressure drop in the double coil MR valve. The proposed double coil MR valve was prototyped and its performance was experimentally evaluated. The new MR valve design has improved the efficiency of double coil MR valve significantly.